Classification of Human Action in a Controlled Environment (International Journal of Engineering and Computer Science, 2014)
It is essential to monitor suspicious activities in certain places. In this paper we propose to develop an intelligent system for visual surveillance which will notify or generate an alarm if a person is found doing a suspicious activity. The system will make use of computer vision concepts like human motion analysis for posture recognition which involves certain suspicious activity.